The repair and regeneration mechanism of platelet-rich fibrin-promoting tissue after alveolar bone defect through the notch pathway: Mechanism alveolar bone defect through the notch pathway - Li, Tao; Long, Hui; Niu, Wei; Feng, Bo (Cellular and Molecular Biology, 2023)
This work investigated the effects of platelet-rich fibrin (PRF) combined with bone mesenchymal stem cells (BMSCs) on the repair of alveolar bone defect (ABD) and the related mechanism of the Notch1/Wnt3a signaling pathway. 28 healthy male New Zealand white rabbits were selected to prepare the BMSCs and PRF. Rabbits were rolled into a combination group (implanted with PRF + BMSCs for treatment), a PRF group (treated with PRF) a BMSC group (BMSCs for treatment), and a control group (Ctrl group, no material implantation), with 7 rabbits in each. The Notch1, Wnt3a, bone morphogenetic protein 9 (BMP9), and p-JNK in rabbits in various groups were compared. It was found that Notch1 and Wnt3a in the combination group were sharply higher than those in the PRF and BMSC groups at postoperative 5 and 10 weeks, exhibiting great differences (P<0.05). The osteocalcin (OCN) and alkaline phosphatase (ALP) in the combination group were higher based on those in the PRF group, BMSC group, and Ctrl group (all P<0.05). Meanwhile, BMP9 and P-JNK proteins in the combination group were much higher than those in the PRF, BMSC, and Ctrl groups, presenting obvious differences (P<0.05). The results revealed that PRF + BMSCs could more effectively downregulate the Notch1 and Wnt3a and activate the Notch1/Wnt3a signaling pathway, thus promoting the osteogenesis of ABD and improving the repair effect.